A real‐life experience as a proof of Guselkumab effectiveness and safety in patients with moderate to severe psoriasis. Issue 4 (8th February 2022) - Michelucci, Alessandra; Manzo Margiotta, Flavia; Panduri, Salvatore; Tonini, Annalisa; Romanelli, Marco; Morganti, Riccardo; Janowska, Agata; Dini, Valentina
Abstract: Psoriasis is a skin disorder characterized by chronic inflammation driven by different immunologic pathways, among which the IL‐23/Th17 axis plays a pivotal role. For this reason, the use of IL23p19 inhibitors in psoriasis treatment has been evaluated over the years. Guselkumab, a totally human IgG1 lambda monoclonal antibody, that selectively blocks the p 19 subunit of IL‐ 23 has demonstrated high efficacy and safety throughout several, randomized, double‐blind phase III trials (VOYAGE 1 and 2, NAVIGATE and ECLIPSE). We designed a single‐center retrospective cohort study in a population consisting of 46 patients followed from December 2018 to April 2021. After a diagnosis of moderate to severe psoriasis, all the patients were considered suitable to receive treatment with Guselkumab. In our population, among those who achieved clinical improvement in terms of Psoriasis Area Severity Index (PASI), PASI 75, 90, and 100 were achieved on average on weeks 14, 19, 21 respectively. We then analyzed a subgroup of our population, consisting of 35 patients, who had an identical follow‐up time of 28 weeks, thus observing the trend in mean PASI at subsequent assessments and the number of patients who had reached PASI 75, PASI 90, and PASI 100 at week 4 (10; 3; 1), week 12 (12; 13; 11), week 20 (7; 6; 2), and week 28 (1; 4; 6), respectively. The results obtained are in line with those obtained from previous studies, thus confirming that Guselkumab is an excellent choice in terms of security, long‐term efficacy, and overall tolerance.